2018
DOI: 10.1016/j.steroids.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of loss of SOAT2 function on disease progression in the lysosomal acid lipase-deficient mouse

Abstract: Although only a small proportion of cholesterol in the body is esterified, in several diseases marked expansion of the esterified cholesterol (EC) pool occurs. These include Wolman disease (WD) and Cholesteryl Ester Storage Disease (CESD) which both result from mutations in LIPA, the gene that encodes lysosomal acid lipase (LAL). The respective contributions that our three cholesterol esterifying enzymes make to EC production, especially in disorders like CESD, are not well defined. The current studies represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Absence of SOAT2 blunted the degree of hepatomegaly in NPC1-deficient mice. Previous studies showed that SOAT2 deficiency alone in adult chow-fed mice had no consistent impact on liver mass (36,59). In contrast, by early adulthood, NPC1 mutant mice fed a chow diet typically exhibit an increased mass of the liver in particular, and to a lesser extent of the spleen and lungs but not of the small intestine (55,57).…”
Section: Degree Of Change In Hepatic Mrna Expression Levels Formentioning
confidence: 96%
See 1 more Smart Citation
“…Absence of SOAT2 blunted the degree of hepatomegaly in NPC1-deficient mice. Previous studies showed that SOAT2 deficiency alone in adult chow-fed mice had no consistent impact on liver mass (36,59). In contrast, by early adulthood, NPC1 mutant mice fed a chow diet typically exhibit an increased mass of the liver in particular, and to a lesser extent of the spleen and lungs but not of the small intestine (55,57).…”
Section: Degree Of Change In Hepatic Mrna Expression Levels Formentioning
confidence: 96%
“…Studies in a mouse model for CESD showed that pharmacological or genetic suppression of SOAT2 function resulted in a marked reduction in hepatic EC sequestration with significantly improved liver function (36,38). Therefore, in the current studies we investigated the potential impact of eliminating SOAT2-driven cholesterol esterification on hepatic UC entrapment and liver function in an NPC1-mutant mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of the maxi-K channel activity of penitrems, lolitrems and shearinines may be associated with their tremorgenic effects and cytotoxicity, which require more detailed research to describe. The inhibition of ACAT activity is conducive to developing new drugs for indole diterpenes to prevent atherosclerosis, hypercholesterolemia and fatty liver diseases [ 154 , 155 , 156 , 157 ]. Furthermore, in the chemical class of drugs, the vast majority of active ingredients are natural lead compounds, which need to be further modified in order to achieve medicinal purposes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Although our initial studies with a mouse CESD model focused mainly on the liver and small intestine (Aqul et al, 2014;Chuang et al, 2017;Lopez et al, 2015Lopez et al, , 2018, our observation that in the untreated aging Lal À/À mice, brain weights were significantly lower than in their matching Lal +/+ controls prompted an investigation of whether there were any discernible changes in an array of molecular markers for cholesterol homeostasis in the CNS of this model. While none were detected, further exploration of why brain mass contracted with advancing disease could potentially raise new questions about brain health in those CESD patients whose diagnosis is not made until late age or who have mutations in LIPA that make them less responsive to therapy.…”
Section: Introductionmentioning
confidence: 99%